Pengaruh Rutinitas Membaca Al-Qur’an di Pagi Hari Bagi Pembentukan Akhlak Mulia Siswa UPTD SMPN 3 Harau - Fatimatuzzahra Alfati; Ulva Rahmi (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This research aims to examine the influence of the routine of reading the Koran in the morning on the formation of noble morals in students at UPTD SMPN 3 Harau. The research method used is quantitative research with a correlational study design. Data was collected through questionnaires given to students randomly. The research sample involved 150 students from various grade levels. Data analysis was carried out using regression techniques to determine the relationship between the independent variable (routine of reading the Koran in the morning) and the dependent variable (formation of noble morals). The research results show that there is a positive and significant relationship between the routine of reading the Al-Qur'an in the morning and the formation of students' noble morals (p < 0.05). This means that the more often students read the Koran in the morning, the higher their level of developing noble morals. These findings have the implication that the activity of reading the Koran in the morning can be used as an effective method in forming students' noble character and morals. Therefore, it is recommended that educational institutions and parents pay more attention to the implementation of the routine of reading the Koran in the morning as part of efforts to build students' character and morals in the school environment. This research makes an important contribution in the context of developing Islamic religious education in schools, especially in efforts to form individuals with noble morals and character in society.Â